Real-world feasibility of co-administration of RSV, COVID-19, and influenza vaccines in older adults: a VAERS-based analysis - Wei, Zhen; Yu, Shilun (Frontiers in Pharmacology, 2025)
BackgroundRespiratory syncytial virus (RSV), COVID-19, and seasonal influenza represent significant health threats to older adults. These pathogens frequently co-circulate during the same seasons. Co-administration of vaccines targeting these viruses is a practical strategy to enhance vaccination coverage and convenience. However, real-world safety data on the simultaneous administration of RSV, COVID-19, and influenza vaccines in adults aged 60 and older remain limited.ObjectiveThis study aimed to explore the safety profile of co-administration of RSV, COVID-19, and influenza vaccines in adults aged 60 and older. Using data from the U.S. Vaccine Adverse Event Reporting System (VAERS), the study aimed to identify patterns of adverse events following immunization (AEFIs) and generate hypotheses regarding possible safety signals, to guide clinical practice and public health strategies. These findings should be interpreted as hypothesis-generating and require confirmation through robust observational studies.MethodsAEFI reports for individuals aged 60 years or older were retrieved from VAERS between 3 May 2023, and 1 January 2025. Three study cohorts were established: the RSV–COVID-19 co-administration group, the RSV–seasonal influenza co-administration group, and the triple-vaccination group. Four disproportionality analysis methods were applied—reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS)—to detect potential safety signals.ResultsA total of 479, 576, and 194 AEFI reports were gathered from the RSV–COVID-19, RSV–influenza, and triple-vaccination groups, respectively. Female reporters outnumbered male reporters by a factor of 2–3. More than 96% of AEFIs occurred within 30 days post-vaccination, with considerable variation in the onset time distribution. Non-serious AEFIs accounted for 85.6%–88.5%, with the majority of clinical outcomes classified as recovered. At the System Organ Class (SOC) level, AEFIs were primarily concentrated in general disorders and administration site conditions, as well as nervous system disorders and abnormal laboratory findings. Potential safety signals included ear and labyrinth disorders, skin and subcutaneous tissue disorders, and injury, poisoning, and procedural complications. At the Preferred Term (PT) level, commonly reported AEFIs included headache, fatigue, and injection site pain, while potential safety signals included aphasia, oral mucosal blisters, and gait disturbance. Among serious reports, high-confidence signals such as influenza-like illness, cerebrovascular accidents, and muscular weakness were identified across all groups. Some high-confidence signals, including sleep disorders and contusions, were also observed in non-serious reports.ConclusionThe overall safety profile of co-administered RSV, COVID-19, and influenza vaccines in older adults is favorable, with most AEFIs being expected and self-limiting. It is crucial to emphasize that this study is hypothesis-generating; the findings do not prove any causal association between vaccines and the reported adverse events. The potential signals of rare but high-risk events, such as neurological, psychiatric, and cardiovascular complications, must be investigated and confirmed in robust observational studies. Enhanced long-term surveillance is recommended to further understand these potential risks.